THE IMPROVEMENT OF KKNI BASED LEARNING MODEL THROUGH COLLABORATIVE LEARNING IN ENGLISH FOR JOB HUNTING SUBJECT (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
Based on the road map in the field of Education and Family Empowerment (IPPK), one of them is a learning model based on the KKNI curriculum. However, based on field observations, this is not in accordance with the concept of learning in the curriculum. Thus, the specific purpose of this research is to formulate the concept of learning based on the KKNI curriculum at University of Muslim Nusantara (UMN) Al Washliyah. The research method is development research with ADDIE design. The population was all students in the eighth semester of the English language education program academic year 2019/2020, so the sample was taken randomly totaling 30 students. Data collection techniques were questionnaire and observation, with data analysis techniques used IBM SPSS 22 for Windows factor analysis. The results obtained at this stage, it is known that students only choose 2 categories of assessment, which is good enough by 80% (24 students), and not good enough by 20% (6 students) from several indicators including preferences for subjects, difficulties encountered in learning, the atmosphere of learning, learning methods, guidance and direction of the lecturer concerned, the provision of pre-test, post-test and assignments, the suitability of the material with the test and the provision of grades so that the best solution is to design a book containing lecture activities in accordance with the customized KKNI curriculum with subjects especially English for Job Hunting courses with the application of collaborative model so that the learning process becomes interactive, active and attractive.
Keywords: KKNI Curriculum; Collaborative Model; English for Job Hunting